The Asymmetric Effect of Panic Index on Cryptocurrencies - Vurur, Necmiye Serap (Frontiers in Applied Mathematics and Statistics, 2021)
The Covid 19 pandemic is the first major crisis facing cryptocurrencies. Therefore, the reaction of the cryptocurrency markets is important. News about epidemics affects investors ' decisions. The relationship between the panic index created from the news about the Covid 19 pandemic and the three major cryptocurrencies with the largest share in the cryptocurrency market was investigated by ARDL and Hatemi-J asymmetric causality test. According to the results of the Hatemi-J causality analysis, positive shocks in the panic index are the cause of negative shocks for all cryptocurrencies. In other words, increases in the panic index are caused to fall the value of Bitcoin, Ethereum, and Ripple cryptocurrencies decrease. The results show that cryptocurrencies were not a safe haven for the investor during the Covid 19 period, as they acted similarly to other financial assets.